2015
DOI: 10.2147/ppa.s77730
|View full text |Cite
|
Sign up to set email alerts
|

Design, construction, and implementation of an online platform for patients with type 1 diabetes: EncoDiab

Abstract: PurposeThe purpose of this study was to develop, build, and implement a virtual platform equipped with practical tools, relevant contents, and communication rooms, with the aim of facilitating patients’ self-management of type 1 diabetes mellitus (T1DM).Materials and methodsThe design of the platform was based on the suggestions of T1DM patients who were being managed at two reference hospitals. Patients’ needs and preferences were identified in group discussion sessions. Before having access to the platform, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…However, it did not prove sensitive to change in patients with type 1 diabetes participating in a virtual platform designed to facilitate self-management (Alvarado-Martel et al, 2015a). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it did not prove sensitive to change in patients with type 1 diabetes participating in a virtual platform designed to facilitate self-management (Alvarado-Martel et al, 2015a). …”
Section: Introductionmentioning
confidence: 99%
“…The ADDQol has shown validity for discriminating between patients with type 2 diabetes receiving insulin or oral drugs and between those with better or worse glycemic control (Sundaram et al, 2007 ) and has shown sensitivity to change following a therapeutic education program (DAFNE Study Group, 2002 ). However, it did not prove sensitive to change in patients with type 1 diabetes participating in a virtual platform designed to facilitate self-management (Alvarado-Martel et al, 2015a ).…”
Section: Introductionmentioning
confidence: 99%
“…several telemedicine systems exist, very few multi-component T1D telemedicine systems targeting emerging adults have been described in the literature, and those that are reported are not fully comprehensive technology-based systems [15][16][17][18][20][21][22][23][24][25]. Additionally, demographic data on race or ethnicity were not presented in any of the papers reviewed.…”
mentioning
confidence: 99%